2022
DOI: 10.1681/asn.2022091078
|View full text |Cite
|
Sign up to set email alerts
|

mRNA COVID-19 Vaccines and Their Risk to Induce a Relapse of Glomerular Diseases

Abstract: variants in human genetic disease. Pathway-specific models of podocytopathies and FSGS such as this also highlight the potential in using simpler genetic systems, such as the fly or the zebrafish, as discovery platforms to screen patient-specific therapies for FSGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In addition, a clinical study recently reported that a second or third vaccination is associated with a two-fold increased risk of a flare-up in patients with IgAN, 18 and there is concern that the repeated stimulation of the immune system by SARS-CoV-2 mRNA vaccination may further increase the frequency of recurrence in patients with glomerular diseases. 19 Therefore, the indication for repeated SARS-CoV-2 mRNA vaccinations in patients with IgAN should be carefully determined individually, considering multiple factors, including the severity of microscopic hematuria and the history of postvaccination gross hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a clinical study recently reported that a second or third vaccination is associated with a two-fold increased risk of a flare-up in patients with IgAN, 18 and there is concern that the repeated stimulation of the immune system by SARS-CoV-2 mRNA vaccination may further increase the frequency of recurrence in patients with glomerular diseases. 19 Therefore, the indication for repeated SARS-CoV-2 mRNA vaccinations in patients with IgAN should be carefully determined individually, considering multiple factors, including the severity of microscopic hematuria and the history of postvaccination gross hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…Some forms of podocytopathy have also been associated with COVID-19 vaccines. Kronbichler et al suggested that there is a temporal and pathogenic association between vaccination and podocytopathies, especially MCD, after the first dose and between other podocytopathies after the second dose [ 22 ]. In a recent systematic review about nephrotic syndrome following COVID-19 immunization, pathogenesis was mainly attributed to the activation of angiotensin-converting enzyme-2 receptors, which leads to podocyte effacement [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference might be related to the booster effect of the vaccine since most presented cases followed the second and third COVID-19 vaccinations. The booster dose of the COVID-19 vaccine increased the absolute risk of glomerular disease compared to naïve exposure [ 21 ]. The supporting evidence was noted in thioridazine-induced ANCA-AAV (leukocytoclastic vasculitis) that occurred 4 weeks after first exposure compared to a shorter duration of 24 h after rechallenging the dose [ 22 ] similar to minocycline-induced cutaneous lupus 1–2 days after repeated exposure compared to 23 months for the first exposure [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The median (IQR) age was 70 ( 22) years, with female predominance (59%). Most cases presented ANCA-GN after receiving the second vaccination (59%) with a median interval gap of 14 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27) days. The mRNA COVID-19 vaccine was the most common (55%), followed by the viral vector vaccine (31%) and inactivated COVID-19 vaccine (14%).…”
Section: Systematic Reviewmentioning
confidence: 99%